2021
DOI: 10.3390/su131810207
|View full text |Cite
|
Sign up to set email alerts
|

UAV Based Spatiotemporal Analysis of the 2019–2020 New South Wales Bushfires

Abstract: Bushfires have been a key concern for countries such as Australia for a long time. These must be mitigated to eradicate the associated harmful effects on the climate and to have a sustainable and healthy environment for wildlife. The current study investigates the 2019–2020 bushfires in New South Wales (NSW) Australia. The bush fires are mapped using Geographical Information Systems (GIS) and remote sensing, the hotpots are monitored, and damage is assessed. Further, an Unmanned Aerial Vehicles (UAV)-based bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Li & Suh [68] examined how the credibility of public social media is affected because of misleading or insignificant information posted just to attract attention. They [67] further supported his findings through careful examinations of various Facebook posts that showed that activeness and argument strength were the key factors of credibility. Nonetheless, social media has proven itself useful and effective in times of natural hazard-related disasters.…”
Section: Social Media Analytics and Natural Hazard-related Disaster Managementmentioning
confidence: 58%
See 1 more Smart Citation
“…Li & Suh [68] examined how the credibility of public social media is affected because of misleading or insignificant information posted just to attract attention. They [67] further supported his findings through careful examinations of various Facebook posts that showed that activeness and argument strength were the key factors of credibility. Nonetheless, social media has proven itself useful and effective in times of natural hazard-related disasters.…”
Section: Social Media Analytics and Natural Hazard-related Disaster Managementmentioning
confidence: 58%
“…During the 2019-2020 bushfires, Australia used unmanned aerial vehicles (UAV) to locate and monitor the bushfires potential path. Ullah [67] stated that the bushfires can be mapped using geographical information systems (GIS) and remote sensing techniques, and subsequently, the hotpots can be monitored, and damages can be assessed. Additionally, the data provided by the UAV's combined with the Australian Bureau of Meteorology and GIS data can be used to develop mapping to identify patterns and fire development [67].…”
Section: Digital Technology and Natural Hazard-related Disaster Managementmentioning
confidence: 99%
“…It focuses on developing computer programs that can access data, and use it to learn for themselves. ML has been used in various fields and domains of science such as agricultural sciences [48], concrete properties prediction [46], bushfire analyses [49], and flood detection and management [13,50], among others. Nevertheless, the applications of ML techniques are very limited or do not exist for mapping the groundwater contamination risk in developing countries, particularly Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ML has been used to construct environmental risk scores beyond standard linear models [55]. In addition, it has been used for engineering risk assessment [56,57], prediction of bioconcentration factors in fish and invertebrates [58], and general monitoring of the environment [49,59].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data storage in the Cloud has also become a critical issue. To manage this, the authors in [ 28 , 29 , 30 ] presented the concept of fog computing. Fog computing is a layer of processing and communication nodes that relieves the Cloud of the burden of multitasking while managing large quantities of user requests.…”
Section: Introductionmentioning
confidence: 99%